La enseñanza del español como segunda lengua (SSL) en una comunidad indígena Wayúu, en Colombia - Malaver, David (2023)
This study characterizes Spanish as a second language teaching methodology implemented by a group of three Watúu teachers from three schools in La Guajira (Colombia) who described their teaching practices based on their beliefs and experiences. We followed the methodology of a qualitative case study. The data was collected through a questionnaire, field notes, individual interviews, and a focus group. Thereafter, results evidence that their teaching methodology is strongly bonded to the community’s cosmovision, setting harmony between traditional and communicative teaching models: likewise, it considers students’ needs and promotes their responsibility to safeguard their culture.